Anatomical Characteristics of Notch Width Index and Femoral Notch Shape in Patients with Anterior Cruciate Ligament Injury - Andrei Kurnia Pranata Sitepu; Chairiandi Siregar; Andriandi Andriandi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Background: Anterior Cruciate Ligament (ACL) injury is a significant orthopedic problem, particularly among young, active individuals. Anatomical factors, such as a narrow intercondylar notch, are considered intrinsic risks. However, findings on the association between the Notch Width Index (NWI) and femoral notch shape with ACL tears vary across populations. This study aimed to describe these anatomical characteristics in patients diagnosed with ACL injury at H. Adam Malik General Hospital, Medan. Methods: A descriptive observational study was conducted using medical records and Magnetic Resonance Imaging (MRI) data of patients treated between January 2023 and December 2024. A total of 64 patients with confirmed ACL injuries who met the inclusion criteria were included. Data on demographics, mechanism of injury, NWI, and femoral notch shape (classified as Type A, U, or W) were collected and analyzed descriptively. Results: The majority of patients were male (71.9%), with a mean age of 27.75 ± 8.35 years. The most common occupations were student (35.9%) and private employee (32.8%). The primary mechanism of injury was sports-related activities (64.1%), with the left knee being more commonly affected (64.1%). The mean NWI for the cohort was 0.28 ± 0.032. The most prevalent femoral notch morphologies were Type W (46.9%) and Type U (42.2%), while Type A was the least common (10.9%). Conclusion: In this cohort, ACL injuries predominantly affect young adult males involved in sports. The average NWI suggests a tendency towards a narrower intercondylar notch. Contrary to some studies, wider notch shapes (Type W and U) were more frequent than the stenotic Type A, indicating potential population-specific anatomical variations.